Bibliometric and visualized analysis of elite controllers based on CiteSpace: landscapes, hotspots, and frontiers - Xingyue Yuan; Yu Lai (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundA unique subset of people living with HIV, known as elite controllers, possess spontaneous and consistent control over viral replication and disease progression in the absence of antiviral intervention. In-depth research on elite controllers is conducive to designing better treatment strategies for HIV. However, comprehensive and illuminating bibliometric reports on elite controllers are rare.MethodsArticles on elite controllers were retrieved from the Web of Science Core Collection. A visualized analysis of this domain was conducted by CiteSpace software. Taking count, betweenness centrality, and burst value as criteria, we interpreted the visualization results and predicted future new directions and emerging trends.ResultsBy December 31, 2022, 843 articles related to elite controllers had been published. The largest contributors in terms of country, institution, and author were the United States (485), Univ Calif San Francisco (87), and Walker B.D. (65), respectively. Migueles S.A. (325) and Journal of Virology (770) were the most cocited author and journal, respectively. Additionally, by summarizing the results of our CiteSpace software analysis on references and keywords, we considered that the research hotspots and frontiers on elite controllers mainly focus on three aspects: deciphering the mechanisms of durable control, delineating the implications for the development of treatments for HIV infection, and highlighting the clinical risks faced by elite controllers and coping strategies.ConclusionThis study performed a bibliometric and visual analysis of elite controllers, identified the main characteristics and emerging trends, and provided insightful references for further development of this rapidly evolving and complex field.